A General View of the Progress of Ethical Philosophy - Anonymous, Anonymous (Analecta Gorgiana, 2010)
The author reviews a volume on ethics, concluding it to be insufficient. Any logical system of ethics and morals must derive from the Bible. The author criticizes the volume's author for his sympathetic treatment of David Hume